The Nitrate-Nitrite-Nitric Oxide Pathway on Healthy Ageing: A Review of Pre-clinical and Clinical Data on the Impact of Dietary Nitrate in the Elderly - Rocha, Bárbara S. (Frontiers in Aging, 2021)
We are living longer. Are we living healthier? As we age, cellular and molecular damage reshape our physiological responses towards environmental and endogenous stimuli. The free radical theory of ageing has been proposed long before ageing has been considered a “scientific discipline” and, since then, has been discussed and upgraded as a major contributor to aberrant ageing. Assuming that ageing results merely from the accumulation of oxidative modifications of biomolecules is not only a simplistic and reductive view of such a complex and dynamic process, but also free radicals and related oxidants are now considered pivotal signalling molecules. The fine modulation of critical signalling pathways by redox compounds demands a novel approach to tackle the role of free radicals in ageing. Nitric oxide (●NO) is a paradigmatic example given its biological functions in cardiovascular, neurologic and immune systems. In addition to the canonical ●NO synthesis by a family of enzymes, nitrate from green leafy vegetables, is reduced to nitrite in the oral cavity which is further reduced to ●NO in the stomach. Boosting this nitrate-nitrite-NO pathway has been shown to improve gastrointestinal, cardiovascular, metabolic and cognitive performance both in humans and in animal models of disease. In the elderly, nitrate-derived ●NO has been shown improve several physiological functions that typically decline during ageing. In this paper, the role of nitrate and derived nitrogen oxides will be discussed while reviewing pre-clinical and clinical data on the cardiovascular, neuronal, musculoskeletal and metabolic effects of nitrate during healthy ageing.